"I Never Felt I Should Think About Freud": From Authority to Liberation in Psychoanalytic Work. Issue 3 (1st September 2016) - Slavin, Jonathan H.
Abstract : Freud's project of personal liberation, the endeavor to free the individual mind, saturates his work. His very definition of adulthood is about "detachment from parental authority." Indeed, in the session reported in this issue, the patient insists that her single meeting with Freud set her free, and that it lasted a lifetime. Yet it would seem that Freud's use of authority as reported in this session contradicts this notion. This brief paper examines the paradox of reconciling Freud's powerful way of working and the use of his authority with the patient's experience of coming to matter as a person for the first time. The paper suggests that maintaining this paradox enables a place in which both therapist and patient are to be able to have their say.